Extractive industries: recognizing and managing the risks in resource-dependent economies - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper analyses the risks facing resource-dependent countries. These include: (i) economic mismanagement (the 'resource curse'); (ii) political mismanagement; (iii) environmental damage (climate change and the destruction of natural capital). It distinguishes 'risk' (which can be addressed probabilistically) from 'uncertainty' (infrequent unpredictable events). Mozambique, with its large natural gas resource, provides examples of all the component risks and uncertainties. The paper then explores the risks and uncertainties arising from the global transition away from fossil fuels to renewable energy. This shift could result in 'stranded countries' as well as 'stranded assets'. Finally, the paper explores the nature of the net-zero transition for metals, including the eventual emergence of new cheaper materials as substitutes for critical, but expensive, minerals. Overall, the paper recommends focusing on a nation's entire portfolio of natural resources in order to minimize the impact of shocks, and to mitigate risks and uncertainties.
Keywords: L71; L72; O13; F34; 330; Africa; extractive industries; debt crisis; mining; natural gas; oil